ANALISIS PRODUK NON SAVING DI ASURANSI SYARI’AH - Abdul Latif (Islamic Economics Journal, 2014)
This paper studies about the concept of Islamic insurance, its development, its funding mechanism and how hibah being a base contract of tabarru’. As long as the insurance institution to be unknown in Islamic history, there are many Islamic literatures concluding that insurance institution is prohibited. However, even there is no any institution like insurance company, but there are some activities performed by Rasulullah SAW related to insurance’s principles, such as togetherness responsibility called aqilah. This system has developed in Arabian society before the birth of Rasulullah SAW. Unless the facts that many problems appeared in the practice of nowadays insurance company which trespass and disturb the rule of Islamic law, which is necessary to be solved, such non saving product that many disruption happened to it and than need to be corrected. For the sake of this matter, the data for the research was needed.